2009
DOI: 10.1016/j.schres.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and its Relationship to Neurocognition, Social Cognition, and Functional Outcome in Schizophrenia

Abstract: Objective-A burgeoning area of research has focused on motivational deficits in schizophrenia, producing hypotheses about the role that motivation plays in the well-known relationship between neurocognition and functional outcome. However, little work has examined the role of motivation in more complex models of outcome that include social cognition, despite our increased understanding of the critical role of social cognition in community functioning in schizophrenia, and despite new basic science findings on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
128
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 40 publications
10
128
0
2
Order By: Relevance
“…However, the analysis of all 36 IPT studies showed that the therapy effects still improved during follow-up. [22][23] Finally, other potentially powerful mediators between cognition and functional outcome are not considered in the analysis, mediators such as motivation 51 or insight (awareness of having a mental illness that requires treatment). 52 And, the analyzed moderator variables in this study -IQ, gender, the duration of treatment -may be influenced by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis of all 36 IPT studies showed that the therapy effects still improved during follow-up. [22][23] Finally, other potentially powerful mediators between cognition and functional outcome are not considered in the analysis, mediators such as motivation 51 or insight (awareness of having a mental illness that requires treatment). 52 And, the analyzed moderator variables in this study -IQ, gender, the duration of treatment -may be influenced by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, an early study by Blanchard and colleagues found no consistent relation of neurocognitive performance with expressive deficits (Blanchard et al, 1994). Moreover, several studies have reported that motivational deficits in schizophrenia were linked to poorer performance on neurocognitive measures (Fervaha et al, 2014a,b;Gard et al, 2009;Nakagami et al, 2008;Roth et al, 2004;Schmand et al, 1994). Recently, studies have investigated correlates of neurocognitive deficits with clinical ratings scales that allow the assessment of both negative symptom dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps consequently, few social cognition studies have employed the GAF scale as an outcome measure (Fett et al, 2011). Furthermore, among the few studies that have used the GAF and found that social cognition is a mediator in the relationship between neurocognition and functioning, most did not account for variation in symptom severity (McGlade et al, 2008;Gard et al, 2009;Schmidt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%